2023
DOI: 10.1038/s41467-023-39142-9
|View full text |Cite
|
Sign up to set email alerts
|

A dorsomedial prefrontal cortex-based dynamic functional connectivity model of rumination

Abstract: Rumination is a cognitive style characterized by repetitive thoughts about one’s negative internal states and is a common symptom of depression. Previous studies have linked trait rumination to alterations in the default mode network, but predictive brain markers of rumination are lacking. Here, we adopt a predictive modeling approach to develop a neuroimaging marker of rumination based on the variance of dynamic resting-state functional connectivity and test it across 5 diverse subclinical and clinical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…Dynamic time-varying FC is a promising avenue to elucidate intricate time-sensitive neuronal mechanisms underlying various states of cognition, disease and consciousness, with greater potential to characterize psychiatric biomarkers compared to traditional static FC alone (Calhoun et al, 2008, 2014; Cohen, 2018; Ganesan et al, 2022; Hutchison et al, 2013). Notably, dynamic FC can outperform static FC in predicting individual differences in rumination using diverse clinical and subclinical datasets (Kim et al, 2023). Our present work demonstrates the utility of dynamic FC in characterizing the time-varying behavior of a whole-brain FC state associated with brooding, a critical symptom and prognostic factor of MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic time-varying FC is a promising avenue to elucidate intricate time-sensitive neuronal mechanisms underlying various states of cognition, disease and consciousness, with greater potential to characterize psychiatric biomarkers compared to traditional static FC alone (Calhoun et al, 2008, 2014; Cohen, 2018; Ganesan et al, 2022; Hutchison et al, 2013). Notably, dynamic FC can outperform static FC in predicting individual differences in rumination using diverse clinical and subclinical datasets (Kim et al, 2023). Our present work demonstrates the utility of dynamic FC in characterizing the time-varying behavior of a whole-brain FC state associated with brooding, a critical symptom and prognostic factor of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating dynamic FC in rumination and MDD have observed links to disrupted FC dynamics of the DMN, CEN and other networks, suggesting impaired neural communications associated with cognitive control, flexibility and self-referential processing. High variability (and low stability) of FC dynamics in DMN regions such as mPFC, hippocampus and PCC (Chen (••) & Yan (•超•), 2021; Kaiser et al, 2016; Kim et al, 2023; Kucyi & Davis, 2014) was associated with increased rumination and mind-wandering across MDD and healthy samples, and dynamic FC of dorsal mPFC was found to strongly predict rumination in MDD (Kim et al, 2023). Similarly, lower stability and shorter dwelling in dynamic FC states with positive FC of DMN, sensorimotor areas and subcortical regions have been associated with MDD pathology (Long et al, 2020; Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This disruption may move the overall of the state from one that supports healthy introspection to one that produces maladaptive rumination. Of the subnetworks highlighted in Figure 3B, the default-mode and fronto-parietal networks have been extensively studied in MDD, with functional and structural alterations reported in areas of each (Kim et al, 2023; Menon, 2011; Sheline et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A connection between sensory network properties and MDD has also been reported (Furey et al, 2013; Zhang et al, 2023), including changes to structure, function, and biochemical properties (Song et al, 2021; Wu et al, 2023). Notably, the visual system has been connected to rumination in some studies (Burkhouse et al, 2017; Kim et al, 2023; Piguet et al, 2014), where activation may reflect memory-related processes (Dijkstra et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…16 A resting-state fMRI model of trait rumination predicted depression scores in adults with major depressive disorder. 82 However, such model predictions do not succeed in all individuals, and population-derived predictive models are most likely to fail in individuals who defy sample stereotypes (e.g. due to sociodemographic and/or clinical factors).…”
Section: Implications For Interpreting Spontaneous Brain Activitymentioning
confidence: 99%